Find the general solution to y"-y'-2y=2e^3x
Given differential equation is
y"-y'-2y=2e^3x
i.e. "\\frac{d\u00b2y}{dx\u00b2}-\\frac{dy}{dx}-2y = 2e^{3x}"
This is a second order linear differential equation.
General solution of it comprises of two parts, complementary function and particular integral.
Complementary function:
Auxiliary equation is m²-m-2=0
=> (m-2)(m+1) = 0
=> m = 2, -1
So complementary function is
"Ae^{-x}+Be^{2x}" , where A, B are constants
Particular integral:
Particular integral of the given differential equation is
"\\frac{1}{D\u00b2-D-2}(2e^{3x})"
= "e^{3x}\\frac{1}{(D+3)\u00b2-(D+3)-2}(2)" [since "\\frac{1}{f(D)}ke^{ax} = e^{ax}\\frac{1}{f(D+a)}k" ]
= "2e^{3x}\\frac{1}{D\u00b2+5D+4}(1)"
= "\\frac{2e^{3x}}{4}\\frac{1}{1+\\frac{D\u00b2+5D}{4}}(1)"
= "\\frac{e^{3x}}{2}[1+\\frac{D\u00b2+5D}{4}]^{-1}(1)"
= "\\frac{e^{3x}}{2}[1-\\frac{D\u00b2+5D}{4}+(\\frac{D\u00b2+5D}{4})^{2}-...\u221e](1)"
= "\\frac{e^{3x}}{2}" , Since Dⁿ(1) = 0 for every natural number n.
So the general solution is
y = "Ae^{-x}+Be^{2x}" + "\\frac{e^{3x}}{2}" , where A, B are arbitrary constants.
Comments
Leave a comment